Eco-friendly packaging training for women farmers group to support digital marketing in Tawangargo Village, Malang Regency - Relawati, Rahayu; Ariadi, Bambang Yudi; Tain, Anas (Community Empowerment, 2021)
Pro-environmental consumers act selectively in choosing products, including packaging. This is both a challenge and an opportunity for the women farmer groups in Tawangargo Village, which produce food and beverage products. The method of this service activity was training and mentoring, transfer of information, monitoring and evaluation. The results of the activity have opened the insights of the female farmer group members to use environmentally friendly packaging and build relationships with suppliers. Especially with the transfer of technology through digital marketing, it will open up wider market opportunities. In its development, the use of environmentally friendly packaging was still combined with conventional packaging to maintain an existing market. On the other hand, actively uploading products in the digital market has not been going well, so it requires further assistance.